Ancient Egyptian Political and Civic History in the Third Pharaohian Family 2780-2680 BC - ٲحمد, شاکر رضا (Polytechnic Journal of Humanities and Social Sciences, 2021)
The period of the authority of the 3rd pharonic family in ancient Egypt 2780-2680 B.C. is considered as the beginning of the old state in Egypt, the period of the authority of this family which is lasted for one century is considered as a very important and outstanding period in the ancient history of Egypt in civilization and politics, because new authority appeared in this period that introduced new and developed things in a way that these new and developed thing have been used and kept later as a base and foundation stone by the later families, among these new thing building pyramids, the way of ruling country and writing and depending on the Calendar. During the period of this family Egypt could get rid of scattering and weakness that was found during the period of the 1st and 2nd family, they could build a strong Egypt and end and control instability in politics in the country, the idea of building Pyramids has been appeared from the king of this family and has been used by the famous engineer (Amhowtab) step by step till has reached to the top during the period of the authority of the forth family which is seen as a civilized and historical masterpiece till now.